2011
DOI: 10.1128/jvi.05524-11
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of BST-2/Tetherin by HIV Infection In Vivo

Abstract: The interferon-inducible antiviral factor BST-2 prevents several enveloped viruses, including HIV, from escaping infected cells. The HIV protein Vpu antagonizes this host defense. Little is known about the expression of BST-2 during HIV infection in vivo and whether it can be modulated to the host's advantage. We studied the expression of BST-2 on blood cells from HIV-infected patients during the acute and chronic phases of disease as well as after antiretroviral treatment (ART). The expression of BST-2 was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 45 publications
12
45
2
Order By: Relevance
“…However, using patient‐derived specimens, it was shown that pandemic HIV‐1 group M express a Vpu variant that antagonizes BST‐2 and CD4 whereas Vpu from non‐pandemic HIV‐1 strains does not antagonize BST‐2 187. Additionally, the neutralizing effect of BST‐2 by Vpu is not absolute in HIV‐1 infected patients 162 and BST‐2 has developed an immune sensing function for HIV‐1 clearance in vivo 41. These data point to the Vpu‐BST‐2 antagonistic interaction as a significant determinant of the ability of either HIV‐1 to promote its spread or of the host to restrict the virus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, using patient‐derived specimens, it was shown that pandemic HIV‐1 group M express a Vpu variant that antagonizes BST‐2 and CD4 whereas Vpu from non‐pandemic HIV‐1 strains does not antagonize BST‐2 187. Additionally, the neutralizing effect of BST‐2 by Vpu is not absolute in HIV‐1 infected patients 162 and BST‐2 has developed an immune sensing function for HIV‐1 clearance in vivo 41. These data point to the Vpu‐BST‐2 antagonistic interaction as a significant determinant of the ability of either HIV‐1 to promote its spread or of the host to restrict the virus.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was made in macrophages derived from rhesus macaques where TLR3 induces the expression of BST‐2 and other restriction factors 161, 162. Although the elements of TLR3‐mediated induction of BST‐2 are yet to be determined, TLR3 induces BST‐2 expression in peripheral blood mononuclear cells (PBMCs) independent of IFN signaling during early immune responses 145 and treatment of PBMCs with poly(I · C), a TLR3 agonist increased BST‐2 levels 162. BST‐2 promoter contains IRF binding elements and a single IRF binding site renders the BST‐2 promoter responsive to induction by IFNα 145.…”
Section: Induction Of Bst‐2 By Toll‐like Receptors (Tlrs)mentioning
confidence: 99%
See 3 more Smart Citations